I123‐FP‐CIT single‐photon emission tomography in patients with long‐standing mixed tremor. Issue 2 (8th October 2012) - de, M.; Renard, D.; Collombier, L.; Boudousq, V.; Kotzki, P. O.; Labauge, P.; Castelnovo, G.
<x xml:space="preserve">Abstract</x> Background and purpose Essential tremor is an abnormal movement characterized by postural and/or kinetic tremor. In some essential tremor patients, rest tremor (RT) is observed but it is not clear if this RT is a feature of essential tremor or a symptom of Parkinson's disease (PD). I123‐FP‐CIT single‐photon emission tomography is used to distinguish essential tremor and PD. Objectives To analyse I123‐FP‐CIT single‐photon emission tomography in a larger series of patients with mixed tremor (i.e. action tremor associated with RT) without PD criteria. Methods We studied 33 consecutives patients (18 men and 15 women) with mixed tremor, clinically and by neuroimaging in all cases. Results I123‐FP‐CIT single‐photon emission tomography was abnormal in 25 of our patients (75.7%) with mixed tremor, and we noted a reduced uptake mostly in the putamen. In our patients with abnormal imaging, RT was unilateral in 52%. In 15 of these 25 patients, putaminal reduced uptake was bilateral and symmetrical. In the other 10 patients, putaminal reduced uptake was asymmetrical or unilateral. In these 10 cases, six had a unilateral RT corresponding to (crossed) predominant reduced uptake in three cases. In our patients with normal imaging, RT was unilateral in 87.5%. Conclusions This study shows that mixed tremor is a heterogeneous entity. The majority of patients with mixed tremor showed nigrostriatal dysfunction on I123‐FP‐CIT single‐photon emission tomography, suggesting that mixed tremor may be a parkinsonian syndrome rather than a clinical variant of essential tremor.